BioSAXS Measurements Reveal That Two Antimicrobial Peptides Induce Similar Molecular Changes in Gram-Negative and Gram-Positive Bacteria - von Gundlach, Andreas; Ashby, Martin P.; Gani, Jurnorain; Lopez-Perez, Paula Matilde; Cookson, Alan Roy; Ann Huws, Sharon; Rumancev, Christoph; Garamus, Vasil M.; Mikut, Ralf; Rosenhahn, Axel; Hilpert, Kai (Frontiers in Pharmacology, 2019)
Two highly active short broad-spectrum AMPs (14D and 69D) with unknown mode of action have been investigated in regards to their effect against the Gram-negative bacteria E. coli and the Gram-positive bacteria methicillin-resistant Staphylococcus aureus (MRSA). Minimal inhibitory concentration (MIC) measurements using a cell density of 108 cfu/ml resulted in values between 16 and 32 µg/ml. Time kill experiments using 108 cfu/ml revealed complete killing, except for 69D in combination with MRSA, where bacterial load was reduced a million times. Small angle X-ray scattering of biological samples (BioSAXS) at 108 cfu/ml was applied to investigate the ultrastructural changes in E. coli and MRSA in response to these two broad-spectrum AMPs. In addition, electron microscopy (EM) was performed to visualize the treated and non-treated bacteria. As expected, the scattering curves generated using BioSAXS show the ultrastructure of the Gram-positive and Gram-negative bacteria to be very different (BioSAXS is not susceptible to the outer shape). After treatment with either peptide, the scattering curves of E. coli and MRSA cells are much more alike. This data in conjunction with the EM indicates that ribosomes might be effected by the treatment as well as changes in the nucleoid occurs. Whereas in EM it is notoriously difficult to observe changes for spherical Gram-positives, the BioSAXS results are superior and reveal strongly similar effects for both peptides induced in Gram-positive as well as Gram-negative bacteria. Given the high-throughput possibility and robust statistics BioSAXS can support and speed up mode of action research in AMPs and other antimicrobial compounds, making a contribution towards the development of urgently needed drugs against resistant bacteria.